Quality in VET in European SMEs : a review of the food processing, retail and tourism sectors in Bulgaria, the Czech Republic, Romania and Slovakia - (:unkn) unknown (Office for Official Publications of the European Communities, 2010)
"Small firms are predominant in all European economies. They are important for employment and hence also for social integration. SMEs are also considered to be important drivers of innovation and experimentation, but tend to carry out little training. [...] Although skills development in SMEs is less than is needed, there is a wide variety of training courses available to them. This potential, and SME limited resources in terms of budget and time for training, increase the importance of the quality of the training provided. For this reason, the present study addresses the questions of whether these firms have a quality approach to training and how, under what conditions, such approaches are or could be introduced and maintained, and what are the internal and external barriers to training. The study sets out to investigate small enterprises in specific sectors (food processing, retail distribution and tourism) in which SMEs, and especially micro and small firms, are present in four newer Member States (Bulgaria, the Czech Republic, Romania and Slovakia) and to draw comparisons between them. [...] A comparison is also drawn between the findings of the present study and those of a previous one on the same theme that covered three "older" Member States: Germany, Ireland and Greece." (Hrsg., BIBB-Doku)
Keywords: S 5.3 Personalentwicklung; S 1.5.3 Betriebliche Weiterbildung; S 3.2.1 KMU, Klein- und Mittlere Unternehmen; L 6 Qualität; T 1.5 International vergleichende Berufsbildungsforschung; G 1.2.4.1.4 Verarbeitendes Gewerbe; G 1.2.4.2.1 Handel, Instandhaltung, Reparatur von Kfz und Gebrauchsgütern; G 1.2.4.2.3 Gastgewerbe; I 2.2.2 Osteuropa; I 2.1 Deutschland; I 2.2.1 Westeuropa; Personalentwicklung; Betriebliche Weiterbildung; On-the-job training; Klein- und Mittelbetrieb; Qualitätssicherung; Nahrungs- und Genussmittelgewerbe; Einzelhandel; Tourismus; Internationaler Vergleich; Bulgarien; Rumänien; Slowakei; Tschechische Republik; Bundesrepublik Deutschland; Irland; Griechenland